Effect of tramadol on testicular histopathological changes and biochemical parameters in male albino Wistar rats - A. Arvinth; S. Umamaheswari; E. Suganya; M. Sakthibalan (Journal of Current Research in Scientific Medicine, 2025)
Background: Chronic use of tramadol is found to produce deleterious effects on the testis. Hence, we aimed to assess the biochemical and testicular histopathological changes produced by long-term administration of tramadol in male albino Wistar rats. Materials and Methods: A total of 30 adult male albino Wistar rats were used. With one as control group, tramadol was injected in four study groups at doses of 15, 30, 60, and 120 mg/kg subcutaneously three doses per week for 45 days. After 45 days, the rats were sacrificed, blood samples were collected from each animal for biochemical analysis, and the testes were excised for histopathological examination. Results: Our results showed that tramadol at a dose of 60 mg/kg and 120 mg/kg decreased the serum testosterone level (P < 0.03; P < 0.01) with an increased serum prolactin level (P < 0.02; P < 0.01) and a decreased serum follicle-stimulating hormone (FSH) levels (P < 0.04; P < 0.01) and luteinizing hormone (LH) (P < 0.02; P < 0.01) compared to the control group with a statistical significance and at a dose of 15 mg/kg and 30 mg/kg showed a mild decrease in testosterone, FSH and LH level with a borderline increase in serum prolactin level. Histopathological examination revealed that animals treated with tramadol at doses of 60 mg/kg and 120 mg/kg showed distinguished histological alterations and abnormal presence of the germinal epithelium with intense damage of seminiferous tubules. Conclusion: This study confirms the negative long-term consequences of tramadol on the testes of male albino Wistar rats. To avoid the drawbacks on male fertility, tramadol should be used cautiously and with proper dose monitoring.